PELAKSANAAN FUNGSI LEGISLASI DEWAN PERWAKILAN RAKYAT DAERAH - Pratama, Tiara Rezki (Jurnal Ilmu Administrasi Negara, 2016)
Function Implementation Legislation Regional Parliament. This study aims to determine how the implementation of the legislative function of the Board of the Regional Parliament kota Pekanbaru. This study uses a qualitative method presented in descriptive form. The informants are legislators Pekanbaru, the Agency legislation and the secretariat of Parliament. Data were collected through interviews, documents relating to the implementation of regional policy. Data were analyzed descriptively qualitative. Results from the study showed that the implementation of the legislative function in the creation and establishment of regional policy has been implemented as intended. However, in the implementation process, there are still shortcomings that come from internal individual and the institution itself.